FEATURES OF EROSION-ACCRETION PROCESSES AND INLET OPENING/CLOSING PHENOMENON IN OLOAN LAGOON (PHU YEN PROVINCE) - Binh, Tran Van; Mau, Le Dinh (Vietnam Journal of Marine Science and Technology, 2012)
In recent years, due to influence of storms and flooding, resulting the processes of erosion - sedimentation at Oloan Lagoon were became the serious hazard for human life and geological environment especially in and around Anhai mouth area. Processes of erosion-accretion were seasonal happening with strong in intensity and complicated in manner. Studying the features of erosion-deposition processes from 2007 to 2010 based on topographic, geological structure and hydrographic data. Study results show that coastal erosion and Anhai Inlet opening occurred during rainy season which concurrent with northeast monsoon and typhoon activity. Whereas, coastal accretion and Anhai Inlet closing occurred during dry season which concurrent with southwest monsoon.